Ether electrolyte based on in-situ polymerization-initiated solvation structure reconstruction effect, preparation method and high-voltage lithium ion battery

By introducing polymerizable monomers containing carbon-carbon double bonds into ether electrolytes, in situ polymerization forms an anion-rich solvation sheath, which solves the problem of poor compatibility of lithium-ion batteries at high voltages, improves the safety and electrochemical performance of the battery, simplifies the production process and reduces costs.

CN120545453APending Publication Date: 2025-08-26SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510562566.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

When existing lithium-ion batteries use lithium metal negative electrodes to match high-voltage positive electrode materials, there are problems such as continuous rupture of the surface solid electrolyte intermediate phase layer, serious side reactions, short circuits and safety hazards caused by the growth of lithium dendrites, and poor compatibility of ether electrolytes with high-voltage positive electrode materials.

Method used

Polymerizable monomers containing carbon-carbon double bonds are introduced into the ether electrolytes, and anion-rich solvation sheath is formed through in-situ polymerization, which improves the high-pressure stability of the electrolyte, and forms a network structure through cross-linking and polymerization to reduce the loss of ether organic solvents.

Benefits of technology

It improves the compatibility of ether electrolyte with high voltage positive electrode, reduces the risk of battery leakage, improves the safety and electrochemical performance of lithium-ion batteries, simplifies production processes, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120545453A_ABST
    Figure CN120545453A_ABST
Patent Text Reader

Abstract

The invention discloses an ether electrolyte based on an in-situ polymerization initiated solvation structure reconstruction effect, a preparation method and a high-voltage lithium ion battery, and relates to the technical field of batteries. The electrolyte comprises the following components: a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, an initiator and a cross-linking agent, wherein the polymerizable monomer containing the carbon-carbon double bond can be polymerized in situ to increase steric hindrance, and a solvation sheath rich in anions is formed in the electrolyte; a high voltage lithium ion battery containing the electrolyte is also provided. According to the preparation method, the polymerizable monomer containing the carbon-carbon double bond and capable of generating in-situ polymerization is added into the ether solvent, and the steric hindrance around the polymerizable monomer containing the carbon-carbon double bond is continuously increased after the polymerizable monomer containing the carbon-carbon double bond is subjected to in-situ polymerization, so that the dissociation capability of the polymerizable monomer containing the carbon-carbon double bond on the lithium salt is reduced; the formation of a lithium ion solvation sheath rich in anions in the electrolyte is promoted, and the high-voltage stability of the ether electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an ether electrolyte based on an in-situ polymerization-induced solvation structure reconstruction effect, a preparation method thereof, and a high-voltage lithium-ion battery. Background Art

[0002] Lithium-ion batteries have been widely used in the field of power batteries due to their advantages such as long cycle life, high specific energy and good stability. The rapid development of new energy technologies has put forward higher requirements on the energy density and safety of lithium-ion batteries. -1 ) and low electrochemical potential (-3.04 V vs. SHE) as the negative electrode, paired with a high-voltage, high-theoretical-capacity positive electrode material, can effectively improve the battery's energy density. However, when using commonly used commercial carbonate electrolytes with lithium metal negative electrodes, during the charge and discharge process, lithium metal deposition and stripping causes the surface solid electrolyte interphase (SEI) to continuously break down and reshape, leading to continuous side reactions, continuous electrolyte consumption, lithium metal negative electrode pulverization, and the formation of "dead lithium." Moreover, the uncontrolled growth of lithium dendrites can cause internal short circuits in the battery, leading to battery fire and explosion. In addition, the large-scale use of low-boiling-point, flammable organic solvents also poses serious safety risks to lithium-ion batteries.

[0003] While ether electrolytes exhibit excellent reduction stability and can form a stable interface with lithium metal anodes, interfacial side reactions with cathode materials at high voltages severely impact the electrochemical performance of lithium-ion batteries. Currently, a common strategy for improving the compatibility of ether electrolytes with high-voltage cathode materials is to form a stable cathode / electrolyte interphase (CEI), derived from an anion-rich lithium ion solvation sheath during charge and discharge. Strategies such as highly concentrated electrolytes (HCEs), locally concentrated electrolytes (LHCEs), and weakly solvating electrolytes (WSEs) can construct anion-rich lithium ion solvation sheaths. However, the high use of lithium salts in HCEs significantly increases electrolyte viscosity, reducing the electrolyte's wetting ability for separators and electrodes. The fluorinated diluents commonly used in LHCEs are expensive, significantly increasing the cost of the electrolyte. WSEs require the rational design of ether molecules, which involves tedious and complex chemical synthesis steps, significantly limiting the practical application of ether electrolytes in lithium metal batteries. Therefore, it is very necessary to develop a low-cost, convenient and high-voltage-resistant lithium-ion battery electrolyte. Summary of the Invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art and to provide an ether electrolyte based on in-situ polymerization-induced solvation structure reconstruction effect, a preparation method thereof, and a high-voltage lithium-ion battery.

[0005] Steric hindrance, also known as the stereo effect, primarily refers to the steric hindrance caused by the proximity of certain atoms or groups in a molecule. Polymerization is a chemical reaction in which monomer molecules form polymers through covalent bonding. The solvation structure of an electrolyte is largely determined by the molecular structure of the solvent and the concentration of the lithium salt. When certain specialized polymerizing monomers are introduced into an ether-based electrolyte, the steric hindrance surrounding the monomers increases during polymerization, which reduces their ability to dissociate from the lithium salt. When these monomers are introduced into an ether electrolyte, the monomers transform into polymers as the polymerization proceeds. This, in turn, promotes the formation of anion-rich lithium ion solvation sheaths in the electrolyte, enhancing the high-voltage stability of the ether electrolyte. Furthermore, the polymerization process can transform the electrolyte from a liquid to a solid state, avoiding the risk of battery leakage while reducing electrolyte volatility, thereby improving the safety of lithium-ion batteries.

[0006] The present invention adds a polymerizable monomer containing a carbon-carbon double bond capable of in situ polymerization to an ether solvent. After in situ polymerization, the steric hindrance surrounding the polymerizable monomer increases. This reduces the dissociation ability of the polymerizable monomer with the carbon-carbon double bond toward lithium salts, promoting the formation of an anion-rich lithium ion solvation sheath in the electrolyte and improving the high-voltage stability of the ether electrolyte. Therefore, the present invention utilizes the steric hindrance changes in the polymerizable monomer caused by in situ polymerization to form an anion-rich solvation structure in the electrolyte, improving the compatibility of the ether electrolyte with high-voltage positive electrodes.

[0007] The technical solutions of the present invention are as follows: The first aspect of the present invention provides an ether electrolyte based on in-situ polymerization-induced solvation structure reconstruction effect, the electrolyte comprising the following components: a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, an initiator, and a cross-linking agent; The polymerizable monomer containing a carbon-carbon double bond can be polymerized in situ to increase steric hindrance and form a solvation sheath rich in anions in the electrolyte.

[0008] Preferably, the components in the electrolyte are calculated in proportion by mass as follows: 4% to 50% of a polymerizable monomer containing a carbon-carbon double bond, 24.5% to 40% of a lithium salt, 24% to 54% of an ether organic solvent, 0.1% to 1% of a cross-linking agent, and 0.1% to 1% of an initiator.

[0009] Preferably, the polymerizable monomer containing a carbon-carbon double bond is one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, carboxyethyl methacrylate, acrylamide methacrylate, acrylamide, isopropyl acrylamide, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl methacrylate, heptafluorobutyl methacrylate, perfluorooctylethyl methacrylate and trimethylsiloxypropyl methacrylate.

[0010] Preferably, the crosslinking agent is one or more of polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, N,N'-methylenebisacrylamide, 1,4-butanediol diacrylate, divinylbenzene, ethylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate and ethylene glycol dimethacrylate.

[0011] Preferably, the initiator is one or more of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide and azobisisobutyramidine hydrochloride.

[0012] Preferably, the lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, lithium bis(fluorooxalatoborate), lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium nitrate, lithium difluorophosphate and lithium trifluoromethanesulfonate.

[0013] Preferably, the ether organic solvent is one or more of 1,2-dimethoxyethane, dimethoxymethane, diethoxymethane, ethyl ether, polyethylene glycol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 1,4-dioxane, 3-methylfuran, ethyl butyl ether and diisoamyl ether.

[0014] A second aspect of the present invention provides a high-voltage lithium-ion battery comprising the electrolyte.

[0015] A third aspect of the present invention provides a method for preparing a high-voltage lithium-ion battery, comprising the following steps: Step 1: uniformly mixing a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, a cross-linking agent, and an initiator under a protective gas atmosphere to obtain an electrolyte precursor solution; Step 2: Assembling a battery with the electrolyte precursor solution, the positive electrode sheet, the negative electrode sheet and the separator; Step 3: leaving the battery at room temperature for a certain period of time, and then heating the battery to polymerize the electrolyte precursor solution to obtain a high-voltage lithium-ion battery.

[0016] Preferably, in step 3, the standing time is 3 h to 4 h, the heating temperature is 40° C. to 60° C., and the heating time is 6 h to 16 h.

[0017] The present invention has at least one of the following beneficial effects: 1. Before polymerization, the electrolyte precursor solution of the present invention has low viscosity, which can achieve efficient infiltration of heavily loaded thick positive electrodes. The in-situ polymerization process can establish ion transmission channels inside the electrode, thereby improving the problem of difficult ion transmission in thick electrodes.

[0018] 2. The present invention uses an in-situ polymerization process of a polymerizable monomer containing a carbon-carbon double bond, which is beneficial to close contact between the electrode / electrolyte interface and reduces the interface impedance. The production process is simple and easy to scale up.

[0019] 3. The polymerizable monomer containing carbon-carbon double bonds of the present invention forms a network structure through cross-linking polymerization, which fixes the free ether small molecules, reduces the loss rate of the ether organic solvent, and ensures stable battery circulation.

[0020] 4. The polymerizable monomer containing a carbon-carbon double bond of the present invention can generate an anion-rich lithium ion solvation sheath in the electrolyte through in situ polymerization, promote the formation of a stable CEI, and thus improve the compatibility of the ether electrolyte with the high-voltage positive electrode.

[0021] 5. The electrolyte of the present invention is transformed from a liquid electrolyte to a solid state during the polymerization process, thereby avoiding the risk of battery leakage and reducing the volatility of the electrolyte, thereby helping to improve the safety of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 1 is a comparison diagram of the electrolyte prepared in Example 1 of the present invention before and after polymerization, wherein (a) before polymerization, (b) after polymerization; Figure 2 1 is a charge and discharge curve diagram of an NCM811||Li battery assembled with the electrolyte in Example 1 of the present invention; Figure 3 1 is a cycle performance diagram of the NCM811||Li battery assembled with the electrolyte in Example 1 of the present invention; Figure 4 1 is a charge and discharge curve diagram of an LCO||Li battery assembled with the electrolyte in Example 4 of the present invention; Figure 5 is a graph showing changes in electrolyte ion conductivity with temperature in Example 6 of the present invention; Figure 6 1 is a charge and discharge curve of an NCM811||Li battery assembled with the electrolyte in Example 7 of the present invention; Figure 7 1 is a charge and discharge curve of the NCM811||Li battery assembled with the electrolyte in Comparative Example 1 of the present invention; Figure 8 1 is a cycle performance diagram of the NCM811||Li battery assembled with the electrolyte in Comparative Example 1 of the present invention; Figure 9 1 is a charge and discharge curve of the NCM811||Li battery assembled with the electrolyte in Comparative Example 2 of the present invention; Figure 10 1 is a cycle performance diagram of the NCM811||Li battery assembled with the electrolyte in Comparative Example 2 of the present invention; Figure 11 3 is a charge and discharge curve of the NCM811||Li battery assembled with the electrolyte in Comparative Example 3 of the present invention; Figure 12 This is a cycle performance diagram of the NCM811||Li battery assembled with the electrolyte in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0024] One embodiment of the present invention provides an ether electrolyte based on in-situ polymerization-induced solvation structure reconstruction effect, the electrolyte comprising the following components: a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, an initiator, and a cross-linking agent; The polymerizable monomer containing a carbon-carbon double bond can be polymerized in situ to increase steric hindrance and form a solvation sheath rich in anions in the electrolyte.

[0025] The present invention adds a polymerizable monomer containing a carbon-carbon double bond that can undergo in-situ polymerization into the electrolyte. After the polymerizable monomer containing a carbon-carbon double bond undergoes in-situ polymerization, the steric hindrance around the polymerizable monomer containing a carbon-carbon double bond will continue to increase, which will lead to a decrease in the dissociation ability of the polymerizable monomer containing a carbon-carbon double bond towards lithium salts, and will promote the formation of a lithium ion solvation sheath rich in anions in the electrolyte, thereby improving the high-voltage stability of the ether electrolyte, that is, improving the compatibility of the ether electrolyte with the high-voltage positive electrode, thereby solving the problem that the ether electrolyte cannot be used under high voltage conditions.

[0026] In some embodiments, the components of the electrolyte are present in the following proportions by mass: 4% to 50% polymerizable monomer containing a carbon-carbon double bond, 24.5% to 40% lithium salt, 24% to 54% ether organic solvent, 0.1% to 1% crosslinker, and 0.1% to 1% initiator. Preferably, the components of the electrolyte are present in the following proportions by mass: 10% to 40% polymerizable monomer containing a carbon-carbon double bond, 28% to 39% lithium salt, 30% to 50% ether organic solvent, 0.2% to 0.9% crosslinker, and 0.2% to 0.9% initiator. More preferably, the components of the electrolyte are present in the following proportions by mass: 20% to 30% polymerizable monomer containing a carbon-carbon double bond, 30% to 35% lithium salt, 35% to 45% ether organic solvent, 0.4% to 0.8% crosslinker, and 0.4% to 0.8% initiator. Specifically, the proportions of the components in the electrolyte are calculated by mass as follows: 20% polymerizable monomer containing carbon-carbon double bonds, 30% lithium salt, 49% ether organic solvent, 0.5% cross-linking agent, and 0.5% initiator; or, 30% polymerizable monomer containing carbon-carbon double bonds, 35% lithium salt, 44.6% ether organic solvent, 0.2% cross-linking agent, and 0.2% initiator; or, 25% polymerizable monomer containing carbon-carbon double bonds, 30% lithium salt, 44.6% ether organic solvent, 0.2% cross-linking agent, and 0.2% initiator.

[0027] In some embodiments, the polymerizable monomer containing a carbon-carbon double bond is one or more of methyl methacrylate (MMA), ethyl methacrylate (EMA), propyl methacrylate (PMA), n-butyl methacrylate (BMA), isobutyl methacrylate (IBMA), tert-butyl methacrylate (TBMA), hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate (HPMA), carboxyethyl methacrylate (CEMA), acrylamide methacrylate (AMA), acrylamide (AM), isopropyl acrylamide (NIPAM), trifluoroethyl methacrylate (TFMA), hexafluorobutyl methacrylate (HFMA), hexafluoroisopropyl methacrylate (HFIPMA), heptafluorobutyl methacrylate (HFBMA), perfluorooctylethyl methacrylate (FMA), and trimethylsiloxypropyl methacrylate (TRIS).

[0028] In some embodiments, the cross-linking agent is one or more of polyethylene glycol dimethacrylate (PEGDMA), trimethylolpropane trimethacrylate (TMPTMA), pentaerythritol triacrylate (PETA), pentaerythritol tetraacrylate (PETTA), N,N'-methylenebisacrylamide (MBA), 1,4-butanediol diacrylate (BDDA), divinylbenzene (DVB), ethylene glycol diacrylate (EGDA), polyethylene glycol diacrylate (PEGDA), trimethylolpropane triacrylate (TMPTA), and ethylene glycol dimethacrylate (EGDMA).

[0029] In some embodiments, the initiator is one or more of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, and azobisisobutyramidine hydrochloride.

[0030] In some embodiments, the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), lithium perchlorate (LiClO4), lithium bis(fluorooxalatoborate) (LiDFOB), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalatoborate) (LiBOB), lithium nitrate (LiNO3), lithium difluorophosphate (LiPO2F2), and lithium trifluoromethanesulfonate (LiOTf).

[0031] In some embodiments, the ether organic solvent is one or more of 1,2-dimethoxyethane (DEM), dimethoxymethane (DMM), diethoxymethane (DEM), diethyl ether (Et2O), polyethylene glycol (Mw = 1000, 2000, 4000, etc.), ethylene glycol monomethyl ether (EGME), ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), diethylene glycol dimethyl ether (DEGDME), diethylene glycol diethyl ether (DEGDEE), triethylene glycol dimethyl ether (TEGDME), triethylene glycol diethyl ether (TEGDEE), tetraethylene glycol dimethyl ether (G4), tetrahydrofuran (THF), tetrahydropyran (THP), 1,3-dioxolane (DOL), 1,4-dioxane (DIOX), 3-methylfuran (3-MF), ethyl butyl ether (EBE), and diisoamyl ether (DIPE).

[0032] Another embodiment of the present invention provides a high-voltage lithium-ion battery including the electrolyte.

[0033] The ether electrolyte of the present invention can be used to prepare high-voltage lithium-ion batteries. The ether electrolyte will not cause serious interfacial side reactions with the positive electrode material under high voltage. The prepared high-voltage lithium-ion battery has stable performance, excellent electrochemical performance, high safety and low cost.

[0034] In some embodiments, the high-voltage lithium-ion battery further includes a positive electrode, a negative electrode, and a separator.

[0035] In some embodiments, the positive electrode material is one or more of lithium cobalt oxide, nickel cobalt manganese, and nickel cobalt aluminum ternary positive electrode materials.

[0036] In some embodiments, the negative electrode material is one or more of metallic lithium, silicon-carbon negative electrode material, lithium titanate, and graphite.

[0037] In some embodiments, the separator is one or more of a polyethylene porous membrane, a polypropylene porous membrane, a polyethylene / polypropylene three-layer composite membrane, and a glass fiber separator.

[0038] Another embodiment of the present invention provides a method for preparing a high-voltage lithium-ion battery, comprising the following steps: Step 1: uniformly mixing a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, a cross-linking agent, and an initiator under a protective gas atmosphere to obtain an electrolyte precursor solution; Step 2: Assembling a battery with the electrolyte precursor solution, the positive electrode sheet, the negative electrode sheet and the separator; Step 3: leaving the battery at room temperature for a certain period of time, and then heating the battery to polymerize the electrolyte precursor solution to obtain a high-voltage lithium-ion battery.

[0039] The preparation method of the present invention is simple, highly practical, and suitable for industrial production. The prepared high-voltage lithium-ion battery has stable performance, excellent electrochemical performance, and high safety.

[0040] In some embodiments, in step 1, a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, a crosslinking agent, and an initiator are mixed under a nitrogen atmosphere and stirred at a speed of 500-1000 r / min for 0.5-2 h to obtain an electrolyte precursor solution.

[0041] In some embodiments, in step 3, the standing time is 3 h to 4 h, the heating temperature is 40° C. to 60° C., and the heating time is 6 h to 16 h.

[0042] The present invention is further described in detail below with reference to specific examples, but the present invention is not limited to the following specific examples.

[0043] It should be noted that: 1. Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0044] 2. The performance of the lithium-ion battery electrolytes prepared in the following examples was tested as follows: The ionic conductivity was measured using an AC impedance spectroscopy (EIS) method on a CHI 760 electrochemical workstation using a stainless steel / diaphragm / stainless steel battery assembled with stainless steel as electrodes and a 50-μm-thick polytetrafluoroethylene membrane with 10-mm-diameter pores as the diaphragm. The charge-discharge cycle test of the lithium battery was performed on a LAND battery charge-discharge test system.

[0045] Example 1: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.935 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol diethyl ether (0.842 g), and then add pentaerythritol tetraacrylate (0.014 g) and azobis(isoheptyl)nitrile (0.014 g) to obtain an electrolyte precursor solution.

[0046] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0047] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0048] The optical photograph of the electrolyte prepared in Example 1 before polymerization is as follows: Figure 1 As shown in (a), the optical photograph after polymerization is as follows Figure 1 As shown in (b) in Figure 1 It can be seen that the electrolyte is liquid before polymerization and solidifies after thermally induced polymerization to obtain a gel-like solid electrolyte, indicating that the electrolyte of the present invention can be solidified by in-situ polymerization after heating.

[0049] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 5.277×10 -4 Scm -1 .

[0050] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 2 As shown in Figure 2, the NCM811||Li battery has a capacity of 185.3 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 The discharge capacity and cycle performance of Figure 3This shows that the electrolyte of the present invention has excellent discharge specific capacity and cycle performance, improves the compatibility of ether electrolytes with high-voltage positive electrodes, and thus solves the problem that ether electrolytes cannot be used in high-voltage batteries.

[0051] Example 2: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.935 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol diethyl ether (1.053 g), and then add pentaerythritol tetraacrylate (0.012 g) and azobis(isoheptyl)nitrile (0.012 g) to obtain an electrolyte precursor solution.

[0052] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0053] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0054] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 8.799×10 -4 Scm -1 .

[0055] Example 3: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.935 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol diethyl ether (1.398 g), and then add pentaerythritol tetraacrylate (0.012 g) and azobis(isoheptyl)nitrile (0.012 g) to obtain an electrolyte precursor solution.

[0056] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0057] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0058] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 1.838×10 -3 Scm -1 .

[0059] Example 4: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.935 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol diethyl ether (0.842 g), and then add pentaerythritol tetraacrylate (0.012 g) and azobis(isoheptyl)nitrile (0.012 g) to obtain an electrolyte precursor solution.

[0060] Step 2: Assemble the LCO||Li battery using the above-mentioned precursor solution, LCO positive electrode, lithium sheet, and glass fiber separator.

[0061] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0062] The LCO||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 4 At 0.1 C, in the voltage range of 2.8~4.3 V, the LCO||Li battery has a capacity of 144.8 mAh g -1 discharge capacity.

[0063] Example 5: This example is used to illustrate the preparation method of an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, and includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.748 g) and lithium bis(fluorooxalatoborate) (0.144 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol diethyl ether (0.842 g), and then add pentaerythritol tetraacrylate (0.012 g) and azobis(isoheptyl)nitrile (0.012 g) to obtain an electrolyte precursor solution.

[0064] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0065] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0066] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests. The NCM811||Li battery had a charge and discharge capacity of 152.4 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 discharge capacity.

[0067] Example 6: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(trifluoromethylsulfonyl)imide (0.800 g) in trifluoroethyl methacrylate (0.116 g) and polyethylene glycol (Mw=2000) (1.000 g), and then add pentaerythritol tetraacrylate (0.001 g) and azobis(isoheptyl)nitrile (0.001 g) to obtain an electrolyte precursor solution.

[0068] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0069] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0070] The obtained electrolyte was subjected to ionic conductivity test, and the obtained ionic conductivity versus temperature curve is shown as follows: Figure 5 As shown, the electrolyte obtained at room temperature has a -4 S cm -1 .

[0071] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests. At 0.1 C, in the voltage range of 2.8~4.3 V, the NCM811||Li battery had a capacity of 162.7 mAh g -1 discharge capacity.

[0072] Example 7: This example is used to illustrate the preparation method of the ether high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, which includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.935 g) in trifluoroethyl methacrylate (1.387 g) and ethylene glycol dimethyl ether (0.867 g), and then add pentaerythritol tetraacrylate (0.012 g) and azobis(isoheptyl)onitrile (0.012 g) to obtain an electrolyte precursor solution.

[0073] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0074] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0075] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 6 As shown in Figure 2, the NCM811||Li battery has a capacity of 148.9 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 discharge capacity.

[0076] Example 8: This example is used to illustrate the preparation method of an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, and includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.374 g) and lithium bis(fluorooxalatoborate) (0.144 g) in hexafluoroisopropyl methacrylate (0.058 g) and ethylene glycol dimethyl ether (0.867 g), and then add pentaerythritol tetraacrylate (0.001 g) and azobis(isoheptyl)nitrile (0.001 g) to obtain an electrolyte precursor solution.

[0077] Step 2: Use the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator to assemble NCM811||Li battery for charge and discharge test.

[0078] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0079] The ionic conductivity of the electrolyte obtained was tested, and the ionic conductivity of the electrolyte obtained at room temperature was 0.42×10 -4 S cm -1 .

[0080] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests. At 0.1 C, in the voltage range of 2.8~4.3 V, the NCM811||Li battery had a capacity of 161.6 mAh g -1 discharge capacity.

[0081] Example 9: This example is used to illustrate the preparation method of an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, and includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.748 g) and lithium bis(fluorooxalatoborate) (0.144 g) in tert-butyl methacrylate (0.875 g) and ethylene glycol dimethyl ether (0.867 g), and then add pentaerythritol tetraacrylate (0.009 g) and azobis(isoheptyl)nitrile (0.009 g) to obtain an electrolyte precursor solution.

[0082] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0083] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0084] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests. The NCM811||Li battery had a capacity of 155.3 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 discharge capacity.

[0085] Example 10 This example is used to illustrate the preparation method of an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in-situ polymerization disclosed in the present invention, and includes the following steps: Step 1: Dissolve lithium bis(fluorosulfonyl)imide (0.561 g) in isobutyl methacrylate (0.886 g) and ethylene glycol diethyl ether (0.842 g), and then add pentaerythritol tetraacrylate (0.009 g) and azobis(isoheptyl)nitrile (0.009 g) to obtain an electrolyte precursor solution.

[0086] Step 2: Assemble the NCM811||Li battery using the above-mentioned precursor solution, NCM811 positive electrode, lithium sheet, and glass fiber separator.

[0087] Step 3: Place the assembled battery at room temperature for 4 hours, then place the battery in a 50°C forced air drying oven and heat it for 12 hours to ensure that polymerization is complete, thereby obtaining an ether-based high-voltage lithium-ion battery based on the solvation structure reconstruction effect induced by in situ polymerization.

[0088] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests. At 0.1 C, in the voltage range of 2.8~4.3 V, the NCM811||Li battery had a capacity of 172.3 mAh g -1 discharge capacity.

[0089] Comparative Example 1 The only difference from Example 1 is that trifluoroethyl methacrylate is not added, and the other aspects are the same as Example 1.

[0090] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 8.323×10 -4 Scm -1 .

[0091] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 7 As shown in Figure 2, the NCM811||Li battery has a capacity of 153.5 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 The discharge capacity and cycle performance of Figure 8 shown.

[0092] Comparing Comparative Example 1 with Example 1, it can be seen that since trifluoroethyl methacrylate is not added in Comparative Example 1, the electrolyte prepared is liquid at this time, and the ionic conductivity becomes higher, but the discharge specific capacity and cycle performance of the assembled NCM811||Li battery become worse.

[0093] Comparative Example 2 The only difference from Example 1 is that trifluoroethyl methacrylate is changed to 0.08 g, and the rest is the same as Example 1.

[0094] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 7.352×10 -4 Scm -1 .

[0095] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 9 As shown in Figure 2, the NCM811||Li battery has a capacity of 142.2 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 The discharge capacity and cycle performance of Figure 10shown.

[0096] Comparing Comparative Example 2 with Example 1, it can be seen that in Comparative Example 2, since the amount of trifluoroethyl methacrylate added is too small (2.5%), the ionic conductivity becomes higher, but the discharge specific capacity and cycle performance of the assembled NCM811||Li battery become worse.

[0097] Comparative Example 3 The only difference from Example 1 is that trifluoroethyl methacrylate is changed to 2 g, and the rest is the same as Example 1.

[0098] The electrolyte ion conductivity was tested and the electrolyte ion conductivity at room temperature was 4.365×10 -4 Scm -1 .

[0099] The NCM811||Li battery assembled with the obtained electrolyte was subjected to charge and discharge tests, and the resulting capacity-voltage curve is shown in Figure 2. Figure 11 As shown in Figure 2, the NCM811||Li battery has a capacity of 169.43 mAh g in the voltage range of 2.8~4.3 V at 0.1 C. -1 The discharge capacity and cycle performance of Figure 12 shown.

[0100] Comparing Comparative Example 3 with Example 1, it can be seen that in Comparative Example 3, due to the excessive addition of trifluoroethyl methacrylate (62.7%), the ionic conductivity of the prepared electrolyte becomes smaller, and the discharge specific capacity and cycle performance of the assembled NCM811||Li battery become worse.

[0101] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. An ether electrolyte based on in-situ polymerization-induced solvation structure reconstruction effect, characterized in that: The electrolyte comprises the following components: a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, an initiator and a cross-linking agent; The polymerizable monomer containing a carbon-carbon double bond can be polymerized in situ to increase steric hindrance and form a solvation sheath rich in anions in the electrolyte.

2. The electrolyte according to claim 1, characterized in that The components of the electrolyte are calculated by mass fraction as follows: 4% to 50% of a polymerizable monomer containing a carbon-carbon double bond, 24.5% to 40% of a lithium salt, 24% to 54% of an ether organic solvent, 0.1% to 1% of a cross-linking agent, and 0.1% to 1% of an initiator.

3. The electrolyte according to claim 1, characterized in that The polymerizable monomer containing a carbon-carbon double bond is one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, carboxyethyl methacrylate, acrylamide methacrylate, acrylamide, isopropyl acrylamide, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl methacrylate, heptafluorobutyl methacrylate, perfluorooctylethyl methacrylate and trimethylsiloxypropyl methacrylate.

4. The electrolyte according to claim 1, characterized in that The crosslinking agent is one or more of polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, N,N'-methylenebisacrylamide, 1,4-butanediol diacrylate, divinylbenzene, ethylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate and ethylene glycol dimethacrylate.

5. The electrolyte according to claim 1, characterized in that The initiator is one or more of potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide and azobisisobutyramidine hydrochloride.

6. The electrolyte according to claim 1, characterized in that The lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, lithium bis(fluorooxalatoborate), lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium nitrate, lithium difluorophosphate and lithium trifluoromethanesulfonate.

7. The electrolyte according to claim 1, characterized in that The ether organic solvent is one or more of 1,2-dimethoxyethane, dimethoxymethane, diethoxymethane, ethyl ether, polyethylene glycol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 1,4-dioxane, 3-methylfuran, ethyl butyl ether and diisoamyl ether.

8. A high voltage lithium ion battery, characterized in that: The electrolyte comprises the electrolyte according to any one of claims 1 to 7.

9. The method for preparing a high-voltage lithium-ion battery according to claim 8, wherein: The following steps are involved: Step 1: uniformly mixing a polymerizable monomer containing a carbon-carbon double bond, a lithium salt, an ether organic solvent, a cross-linking agent, and an initiator under a protective gas atmosphere to obtain an electrolyte precursor solution; Step 2: Assembling a battery with the electrolyte precursor solution, the positive electrode sheet, the negative electrode sheet and the separator; Step 3: leaving the battery at room temperature for a certain period of time, and then heating the battery to polymerize the electrolyte precursor solution to obtain a high-voltage lithium-ion battery.

10. The preparation method according to claim 9, characterized in that In step 3, the standing time is 3 h to 4 h, the heating temperature is 40° C. to 60° C., and the heating time is 6 h to 16 h.